Design and development of a cd-rom in dynamic functional rehabilitation of the maxillary bones (Revista Nacional de Odontología, 2014)
Introduction: This article is part of a research line entitled “Pedagogy and Didactics in Dental Teaching” carried out in 2012 by the postgraduate dental research group at the Bogotá campus of the Universidad Cooperativa de Colombia. In the context of the era of technology, a teacher-student interaction is made use of when designing, developing and using a teaching tool based on multimedia software, with content-oriented Dynamic Functional Rehabilitation of the Jaws.Objective: To design and produce a cd on Rehabilitation functional dynamics of the jaws (rdfm) for students’ knowledge of orthodontics and functional orthopedics at the Universidad Coop‑ erativa de Colombia. Materials and methods: Technological development study, using a literature search of PubMed and textbooks to organize the topics as a navigational map in seven thematic units: User Manual, Introduction, Definition and Classification, Concepts, Appliances, Self-evaluation and Bibliography. This cd was developed with NeoBook and Flash CS5 programs, generating an executable file for the Windows operating system.Results: Design of a software called “Maxillary Orthopedics for Encapsulation, Technical and Functional Rehabilitation Dynamics of the Jaws”, which will be distributed on a cd.Conclusions: This study showed that there is an alternative in the treatment plan in the Functional Orthopedics and Orthodontics specialization; this can provide a different option when planning and dealing with the different malocclusions.
Keywords: dynamics; encapsulation; functional orthopedics